A behavioral and fMRI examination of the effect of rhythm on reading noun-verb homographs aloud. Issue 7 (9th August 2018) - Gould, Layla; Mickleborough, Marla J.S.; Lorentz, Eric; Ekstrand, Chelsea; Borowsky, Ron
ABSTRACT: These experiments explored the connection between rhythm and reading by examining whether reading is affected by a rhythmic prime that was either congruent or incongruent with the syllabic stress of the target letterstring. Previous research has shown congruency effects but only in a between-item design, which leaves open the possibility of extraneous variables contributing to the effects. The present design used noun-verb homographs ( con flict vs. con flict ), and their corresponding pseudohomophones ( kon flikt vs. kon flikt ). The results demonstrated significant congruency effects, whereby RTs were faster when the prime was congruent with the syllabic stress. The fMRI experiment identified several brain regions that underlie the rhythm-priming effect, and particularly the putamen's involvement given recent research suggesting its role in phonetic decoding. These experiments provide the strongest within-item/within-participant evidence to date that a rhythm prime has an effect on lexical and sublexical reading, and inform our understanding of how rhythm and reading interact.